(untitled) (Third Sector Social Economic Review, 2019)
Ottoman court records, which contain important information and data in socio-cultural and legal terms, are precious written sources reflecting the accumulation of the past day by day. These registry books belonging to legal, administrative and economic life in certain areas not only reveal the local differences but also the records belonging to all regions are observed and the determinations related to the whole country are formed. In this study, the course of economic activities in Kastamonu province was examined in light of similar records. Between the dates of 1673/1850, the official levels of the bakery products which the state has officially determined in Kastamonu have been determined according to the instructions given in the Kastamonu Sher ’Registers. Determined to determine commodity prices, the narh was taken to the registry for carrying the official document qualification. These records are important in determining the commodity prices in Kastamonu Province. Because, by looking at these prices, it is possible that we can not see the reflection of the instabilities in political, military and social developments in the Ottoman Empire in the 17th and 18th centuries. These developments in the Ottoman State led to the fall of the value of money, the increase in prices, in short, inflation. Undoubtedly, Kastamonu Province was also affected by this situation. The result of the instability expressed in the Kastamonu Province during the dates mentioned above is reflected in the results of this study.